Part-load performance modelling of a reheated humid air turbine power cycle - Brighenti, Giovanni D.; Zachos, Pavlos K.; Orts-Gonzalez, Pau Lluis (Elsevier, 2018)
Humid air turbines have previously demonstrated the potential to deliver high efficiency and power output combined with low emissions. This paper investigates the part-load performance of a 40 MW class advanced humid air turbine for power generation applications across a range of operating conditions. The paper investigates the impact of the main burner and reheater burner on the system’s part-load power output and thermal efficiency and provides insights into the behavior of the key modules across the power spectrum of operation including the saturator tower which was never reported previously. The impact of the ambient air and sea water temperature on the cycle’s performance are also investigated. The outcome of the research shows that the thermal efficiency if the system is less than 0.26% penalized when operating down to 50% of the design power output. Sea water temperature was found to have a more notable impact than ambient air temperature on both power output and thermal efficiency Overall, this work constitutes a step ahead in understanding the potential benefits of an advanced humid air turbine system for power generation applications across a range of operating conditions which is not previously shown.
Keywords: humid air turbine; power generation; part-load performance